Combined effect of external damper and cross-tie on the modal response of hybrid two-cable networks. (17th March 2018) - Ahmad, Javaid; Cheng, Shaohong; Ghrib, Faouzi
Abstract: Combining external dampers and cross-ties into a hybrid system to control bridge stay cable vibrations can address deficiencies associated with these two commonly used vibration control solutions while retaining their respective merits. Despite successful implementation of this strategy on a few cable-stayed bridges, behavior of such a structural system is still not fully understood. In the current study, an analytical model of a hybrid system consisting of two parallel taut cables interconnected by a transverse linear flexible cross-tie, with one cable also equipped with a transverse linear viscous damper close to one end support, is developed. The proposed model is validated by an experimental work in the literature and an independent numerical simulation. A parametric study is conducted to comprehend the impact of main design parameters on the performance of a hybrid system in terms of the in-plane frequency, the damping and the degree of mode localization of the system's fundamental mode. In addition, the concept of isoquant curve is applied not only to appreciate the effect of simultaneous variation in main design parameters on the modal behavior of a hybrid system, but also to identify the optimal ranges of these parameters to achieve the required cable vibration control effect. Highlights: Proposed an analytical model for hybrid systems used in cable vibration control. Increase cross-tie flexibility or spacing towards damper maximizes damper effect. Cross-tie flexibility has opposite effect on indicators of system performance. Isoquant curves are applied to identify optimum ranges of system parameters.